(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2019)
Argentine movie Chinese Take Out constitutes both a cultural representation and a signifying practice. As a filmic representation, it allows visual encoding of current eco- nomic and political experience. It depicts cultural stereotyping of Asian (Chinese, specifically), from a Latin American perspective. The film also exemplifies how Asian popular culture is re-interpreted and re-appropriated across national borders in Latin America. The article’s main claim is that the relationship between the two main characters (an Argentine and a Chinese) is symbolic and reflective of the multifaceted character of the international relation between both countries/regions.